2017
DOI: 10.1186/s40792-016-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

An adult case of lymphangioma of the hepatoduodenal ligament mimicking a hepatic cyst

Abstract: BackgroundIntra-abdominal lymphangiomas are rare, benign tumors in adults. This report is the third documented case of a lymphangioma originating in the hepatoduodenal ligament that mimicked a simple liver cyst.Case presentationA 50-year-old woman was admitted with a cystic tumor in the right lobe of her liver and underwent laparoscopic excision of the cyst. Operative findings revealed that the cyst had developed in the hepatoduodenal ligament, not in the liver. A small part of the cystic wall remained on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The morphology was enough to make the diagnosis for most cases[ 13 , 31 ]. Certainly, lymphatic marker, D2-40 (podoplanin), further confirmed the identification of the disease[ 1 , 19 , 32 ]. In addition, endothelial markers, including von Willebrand factor, CD31, and CD34 and two lymphatic markers, LYVE-1 and Prox-1, are recommended through immunohistochemistry staining when it is difficult to distinguish lymphatic vessels from blood vessels[ 1 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The morphology was enough to make the diagnosis for most cases[ 13 , 31 ]. Certainly, lymphatic marker, D2-40 (podoplanin), further confirmed the identification of the disease[ 1 , 19 , 32 ]. In addition, endothelial markers, including von Willebrand factor, CD31, and CD34 and two lymphatic markers, LYVE-1 and Prox-1, are recommended through immunohistochemistry staining when it is difficult to distinguish lymphatic vessels from blood vessels[ 1 ].…”
Section: Discussionmentioning
confidence: 90%
“…Treatments for hepatic lymphangioma include complete resection, partial resection with cleaning cystic fluid, needle aspiration, sclerosing agent injection, liver transplantation, and immunosuppressive drugs for diffused and serious condition[ 11 , 12 , 34 - 36 ]. Partial resection with cleaning cystic fluid and needle aspiration can definitely lead to tumor recurrence[ 32 , 36 ]. The effectiveness of sclerosing agent injection, which is effective for a simple liver cyst, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital or acquired abnormalities of the lymphatic system are the initiating factors causing development of lymphangiomas. Congenital lymphangiomas form due to blockage of the lymphatic system during fetal development resulting in an improper connection of lymphatic channels to the main lymphatic drainage duct [ 4 ], whereas acquired lymphangioma occurs because of an interruption in a previously normal lymphatic drainage system as a result of surgery, trauma, malignancy, and radiation therapy. The congenital form predominately occurs in young children, with 90% found extra-abdominally, such as in the head, neck, and axilla [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, lymphangioma present with an acute abdomen, which can result from obstruction, perforation, or torsion of the bowel secondary to the large volume of the lymphangioma. In case studies, lymphangiomas have been mistaken for liver hematoma [ 6 ], liver cyst [ 7 ], ovarian cyst [ 8 ], and even metastasis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the width of the ligament, we found that there were two periods of accelerated development (4-5 months and 9 monthsnewborns) and a period of slow development (5-8 months). It is worth noting that at some stage of development (6 months), the length of the hepatic-duodenal ligament is even slightly reduced, which can probably be associated with an increase in the adjacent organs -the liver and the duodenum in this period [13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%